The Impact of COVID-19: Become New Entrepreneurs with Online Business - Bima Yatna Anugerah Ramadhani (Yayasan Ilomata, 2021)
The number of unemployed increased dramatically due to COVID-19. This can happen because many companies instruct their employees to work from home and some companies forced to do temporary dismissal and/or lay off their employees to survive during a pandemic. After that, many of people decide to create online business and become entrepreneurs. Products sold can be obtained from other people (be reseller) or make it by themselves. These products will be sold online, both with shopping applications and social media. The purpose of this research is to introduce the advantages of being an entrepreneur with online business and to show how technology affects the business. Therefore, this research tries to analyze the benefits of being an entrepreneur compared to being an employee and to find out how new entrepreneurs manage and market their products by technology during this pandemic. The samples of this research are 10 new entrepreneurs who get temporary dismissal of workers and or lay off from their company and open the online business in Surabaya and Sidoarjo. The methodology of this research is a qualitative methodology by analyzing social media accounts or online shop accounts that entrepreneurs use for selling their products and also conducting online interviews with them to ensure their accuracy. The results of this research indicate that online businesses provide benefits and convenience for entrepreneurs to do business during this pandemic and also give a motivation for entrepreneurs to continue and improve their business if COVID-19 has been completed.